EFEKTIVITAS GERAKAN LITERASI 15 MENIT DALAM MENUMBUHKAN MINAT BACA SISWA AUTIS KELAS IV SLB TNCC BANDA ACEH MATA PELAJARAN BAHASA INDONESIA (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Reading interest is one of the important keys for someone to gain knowledge and information. So by reading, students can get the knowledge that has been provided. The more often a student reads, the broader his knowledge and insight will be. This study aims to determine the effectiveness of the 15 Minute Literacy Movement in Fostering Reading Interest in Class 4 Autistic Students in Indonesian Language Subjects in Narrative Story Text Material at TNCC Banda Aceh Special School. This research is a qualitative research, with data collection techniques including observation, interviews and studies. documentation. The subjects in this study were students of class IV Autism at SLB TNCC Banda Aceh, which consisted of two people, and the data analysis technique was carried out qualitatively with stages including: (1) data reduction, (2) data presentation. (3) Triangulation, and (4) Verification / Conclusion Withdrawal. Based on the results of the study, it is known that the Literacy Movement 15 minutes before the Teaching and Learning Process (PBM) is very effective in cultivating students’ reading interest in autism in class 4. This can be seen from the results of completeness of the indicators of the effectiveness of reading interest, with 15 minutes of Literacy activities for autistic students there are significant changes. in recognizing letters and students’ reading interest increases.